First palaeoneurological study of a sauropod dinosaur from France and its phylogenetic significance - Fabien Knoll; Stephan Lautenschlager; Xavier Valentin; Verónica Díez Díaz; Xabier Pereda Suberbiola; Géraldine Garcia (PeerJ, 2019)
Despite continuous improvements, our knowledge of the palaeoneurology of sauropod dinosaurs is still deficient. This holds true even for Titanosauria, which is a particularly speciose clade of sauropods with representatives known from numerous Cretaceous sites in many countries on all continents. The data currently available regarding the palaeoneurology of titanosaurs is strongly biased towards Gondwanan forms (Argentina above all, but also India, Malawi and Australia). In contrast, the palaeoneurology of Laurasian titanosaurs is known only from a few taxa from Spain and Uzbekistan, despite the discovery in other countries of Laurasia of a number of neurocranial remains that would lend themselves well to investigations of this kind. To fill in this gap in our knowledge, we subjected a titanosaurian braincase from the uppermost Upper Cretaceous of southern France to X-ray computed tomographic scanning, allowing the generation of 3D renderings of the endocranial cavity enclosing the brain, cranial nerves and blood vessels, as well as the labyrinth of the inner ear. These reconstructions are used to clarify the phylogenetic position of the specimen from the Fox-Amphoux-Métisson site. A combination of characters, including the presence of two hypoglossal rami on the endocast, the average degree of development of the dorsal-head/caudal-middle-cerebral vein system and the relatively short and subequal lengths of the ipsilateral semicircular canals of the labyrinth, are particularly revealing in this respect. They suggest that, compared with the few other Laurasian titanosaurs for which in-depth palaeoneurological data are available, the French taxon is more derived than the distinctly more ancient, possibly non-lithostrotian titanosaur from the Uzbek site of Dzharakuduk but more basal than derived saltasaurids, such as the coeval or slightly more recent forms from the Spanish locality of Lo Hueco.